Identifikasi Gaya Belajar Matematika Mahasiswa Program Studi Pendidikan Matematika Institut Pendidikan Soe - Tahuk, Rayner N. W; Taneo, Prida N. L.; Daniel, Farida (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
This study aims to identify the learning styles of students in the mathematics education study program at the Soe Education Institute. This research is a qualitative descriptive study which describes and describes in more detail the students' learning styles. The primary data sources in this study were 86 students of the Soe Education Institute's mathematics education study program class 2016-2019. The secondary data source is the student attendance list. Data collection techniques in this study were in the form of learning style questionnaires, semi-structured interviews and documentation. The results showed that the mathematics learning styles of students in the mathematics education study program were different in each class. The mathematics learning styles of the 2016 students of the class of 2016 tend to be evenly distributed across the three learning styles, namely 35% visual, 30% auditory and 35% kinesthetic. The mathematics learning style of students from the 2017 class of 13 people only tends to 2 learning styles, namely 55% visual and 45% auditory. The mathematics learning styles of students from the 2018 batch of 30 people tend to be evenly distributed across the three learning styles, namely 30% visual, 30% auditory and 40% kinesthetic. The mathematics learning style of students from the 2019 batch of 17 people is dominated by visual learning styles of 59%, then 35% auditory and 6% kinesthetic.